High-frequency operation of pulsatile ventricular assist devices: A computational study on circular and elliptically shaped pumps. Issue 12 (December 2019) - Loosli, Christian; Rupp, Stephan; Thamsen, Bente; Rebholz, Mathias; Kress, Gerald; Meboldt, Mirko; Ermanni, Paolo
Pulsatile positive displacement pumps as ventricular assist devices were gradually replaced by rotary devices due to their large volume and high adverse event rates. Nevertheless, pulsatile ventricular assist devices might be beneficial with regard to gastrointestinal bleeding and cardiac recovery. Therefore, aim of this study was to investigate the flow field in new pulsatile ventricular assist devices concepts with an increased pump frequency, which would allow lower stroke volumes to reduce the pump size. We developed a novel elliptically shaped pulsatile ventricular assist devices, which we compared to a design based on a circular shape. The pump size was adjusted to deliver similar flow rates at pump frequencies of 80, 160, and 240 bpm. Through a computational fluid dynamics study, we investigated flow patterns, residence times, and wall shear stresses for different frequencies and pump sizes. A pump size reduction by almost 50% is possible when using a threefold pump frequency. We show that flow patterns inside the circular pump are frequency dependent, while they remain similar for the elliptic pump. With slightly increased wall shear stresses for higher frequencies, maximum wall shear stresses on the pump housing are higher for the circular design (42.2 Pa vs 18.4 Pa). The calculated blood residence times within the pump decrease significantly with increasing pump rates. A smaller pump size leads to a slight increase of wall shear stresses and a significant improvement of residence times. Hence, high-frequency operation of pulsatile ventricular assist devices, especially in combination with an elliptical shape, might be a feasible mean to reduce the size, without any expectable disadvantages in terms of hemocompatibility.